Lymphocyte to High-Density Lipoprotein Ratio but Not Platelet to Lymphocyte Ratio Effectively Predicts Metabolic Syndrome Among Subjects From Rural China - Yu, Shasha; Guo, Xiaofan; Li, GuangXiao; Yang, Hongmei; Zheng, Liqiang; Sun, Yingxian (Frontiers in Cardiovascular Medicine, 2021)
Background: This study intended to use two novel inflammatory indicators: lymphocyte to high-density lipoprotein cholesterol ratio (LHR) and platelet to lymphocyte ratio (PLR), to predict newly diagnosed metabolic syndrome (MetS) among subjects from rural Northeast China. Methods: Adult participants without MetS at baseline (n = 4,980, age = 52.65 ± 10.21 years; 51.9% men) were originated from the Northeast China Rural Cardiovascular Health Study (NCRCHS). LHR (Q1: ≤1.04; Q2: 1.04–1.35; Q3: 1.35–1.79; Q4: ≥1.79) and PLR (Q1: ≤78.50; Q2: 78.50–107.27; Q3: 107.27–140.00; Q4: ≥140.00) were divided in quartile. Results: After 4.66-year follow-up, 1,194 subjects were diagnosed MetS (cumulative incidence 24.0; 25.8% for female and 22.3% for male, P = 0.002). Newly diagnosed MetS had higher value of hemoglobin and platelet count compared to those without MetS. As for LHR, from Q1 to Q4, there were increasing value of waist circumference (WC), serum triglycerides (TG), rates of current smoking and drinking whereas decreasing value of HDL-C. However, for PLR, rates of current smoking and drinking significantly decreased from Q1 to Q4. Similarly, the value of WC and TG showed a decreasing trend. In a logistic regression analysis, after adjusted for possible confounders, LHR [OR (95% CI) Q2: 1.13 (0.86, 1.48); OR (95% CI) Q3: 1.23 (0.94, 1.61); OR (95% CI) Q4: 1.57(1.20, 2.06)] but not PLR was effective predictor of newly diagnosed MetS among rural Chinese. Conclusion: MetS had closed relationship with inflammation among subjects from rural China. As a novel marker of inflammation, LHR but not PLR might be an effective predictor of newly diagnosed MetS and should be widely used in the epidemiological study.